COM654: Asian politics / Faculty of Communication and Media Studies - UiTM, Faculty of Communication and Media Studies (2016)
This course is designed for students of Communication and Media Studies It will provide students with current developments involving the countries in the Asian region. Special emphasis will be given to various concepts that involve an understanding of ideologies and the origin of political science that dominates the administration of countries in the region. Students will be exposed to various perspectives such as colonization, independence, and current developments. The course also examines the role played by the state in managing the media. It is a symbiotic relationship that exists in many countries in the region despite of different ideologies consumed by the state. The dynamics that shape the relationship among countries in the Asia makes it unique and more challenging compared with other regions of the world.